2008
DOI: 10.2174/1874440000802010005
|View full text |Cite
|
Sign up to set email alerts
|

Motor Representations and Practice Affect Brain Systems Underlying Imagery: An fMRI Study of Internal Imagery in Novices and Active High Jumpers

Abstract: This study used functional magnetic resonance imaging (fMRI) to investigate differences in brain activity between one group of active high jumpers and one group of high jumping novices (controls) when performing motor imagery of a high jump. It was also investigated how internal imagery training affects neural activity. The results showed that active high jumpers primarily activated motor areas, e.g. pre-motor cortex and cerebellum. Novices activated visual areas, e.g. superior occipital cortex. Imagery traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 56 publications
1
85
0
2
Order By: Relevance
“…Yet, according to our results it seems that the imagery strategy is not the crucial factor for the involvement of M1 in motor imagery of a simple hand action suggesting that other factors such as those discussed in the introduction (the personal ability to form and retrieve mental representations, the requirements of the action or the expertise of the participants; Kuhtz-Buschbeck et al, 2003;Olsson et al, 2008;Lotze and Zentgraf, 2010) may determine involvement of M1. For example, it has been suggested that increasing experience in motor imagery induces changes to the activation patterns involving less motor areas and more areas implicated in abstract representations (Lotze and Halsband, 2006).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Yet, according to our results it seems that the imagery strategy is not the crucial factor for the involvement of M1 in motor imagery of a simple hand action suggesting that other factors such as those discussed in the introduction (the personal ability to form and retrieve mental representations, the requirements of the action or the expertise of the participants; Kuhtz-Buschbeck et al, 2003;Olsson et al, 2008;Lotze and Zentgraf, 2010) may determine involvement of M1. For example, it has been suggested that increasing experience in motor imagery induces changes to the activation patterns involving less motor areas and more areas implicated in abstract representations (Lotze and Halsband, 2006).…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, whether kinesthetic or visual imagery is adopted depends on how well subjects may have already developed their internal motor representations (e.g. Olsson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Study 2, which included groups of experienced pianists, experienced ice hockey players, and age-matched controls, did not meet our expectations in that there was no advantage for any of the imagined actions for any group, regardless of their familiarity with the imagined actions (e.g., pianists imagining playing piano, etc.). Compared to novices, experienced athletes and musicians utilize fewer regions of the brain when imagining actions involving the sport or instrument with which both groups have familiarity (e.g., Lotze et al, 2003;Fourkas et al, 2008;Olsson et al, 2008;Wei & Luo, 2010). Although expert brain responses to familiar imagery are fairly consistent within and across individuals (e.g., Langheim et al, 2002), these responses did not result in an enhancement of the SMR in Study 2.…”
Section: Discussionmentioning
confidence: 85%
“…In this paper, we chose to explore the role of action familiarity in modulation of the SMR by drawing from samples of experienced athletes and musicians, given that the effects of long-term motor learning have been studied extensively in these groups already (see Münte et al, 2002, andNakata et al, 2010, for reviews). While imagining actions involving the sport or instrument of their expertise, experienced athletes and musicians produce more focused patterns of brain activation (e.g., Lotze et al, 2003;Milton et al, 2007;Olsson et al, 2008;Wei & Luo, 2010) and report more objectively accurate imagery than novices (e.g., Louis et al, 2012; see also Rieger, 2012). Based on the latter findings, it was expected that familiar imagery would result in a more reliable SMR, and thus higher classification accuracy, than traditional SMRbased BCI imagery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation